BIOLOGICAL CONTROL OF BANDED LEAF AND SHEATH BLIGHT DISEASE (Rhizoctonia solani KUHN) IN CORN WITH FORMULATED Bacillus subtilis BR23 - Amran Muis; Arcadio J. Quimio (Indonesian Journal of Agricultural Science, 2006)
Rhizoctonia solani Kuhn. causing banded leaf and sheath blight diseases is one of the important fungi of corn world wide. The fungus is commonly controlled by using fungicide because no resistant variety available. The objective of the study was to develop a seed treatment formulation of the selected Bacillus subtilis to control R. solani in corn. The study was conducted in the Department of Plant Pathology, College of Agriculture, University of the Philippines Los Bañòs, College, Laguna from May 2004 to August 2005, using sweet corn var. IPB Supersweet as test plant. Corn seeds were surface sterilized for 10 minutes in 1% sodium hypochlorite solution and 5% ethanol, washed thrice with sterile distilled water and air-dried. The seeds were coated with formulated B. subtilis BR23 and used for several experiments, such as evaluation for their germination and growth in the laboratory, effectively on R. solani in the baked and nonbaked field soil under greenhouse condition, and in the microplots artificially infested with R. solani. The treatment was compared with other standard seed treatment of synthetic fungicides such as captan (10 g per kg seeds) and metalaxyl (10 g per kg seeds). The experiments were designed in a completely random design with three replications. Parameters observed were seed germination, plant height, disease scores, and plant yield. Laboratory formulated B. subtilis BR23 used as seed treatment had no detrimental effects on seed germination and seedling vigor. In microplots artificially infested with a selected highly virulent R. solani, seed treatment with the same formulation increased grain yield by 27% compared to that of the control captan seed treatment with 14.4%. The studies showed the potential of B. subtilis BR23 for commercialization as a seed treatment for the control of banded leaf and sheath blight disease (R. solani) in corn.